John Ralph interviewed by Rob Linn - Ralph, John Theodore; Linn, Rob. (2006)
John Ralph, born 1932 in Broken Hill, New South Wales, talks about his family background and childhood; Sir Maurice Mawby's influence; education; Broken Hill during the 1930s and 1940s; family and religious life; Broken Hill's links with Adelaide; the Zinc Corporation in Broken Hill; his work with the Corporation; moving into accountancy; continuation of study with the company, Technical College and the Federal Institute of Accountants; career development for young people in the company; his progress through the company; overview of the Zinc Corporation and relations between Consolidated Zinc, Imperial Smelting and New Broken Hill etc; becoming Secretary of the Housing Scheme; company services for employees; marriage to Barbara in 1959 and move to Melbourne in 1961; working for ConZinc in Melbourne; the first days of Comalco; the mining boom in the 1960s; management studies at Harvard and the Mount Eliza School, with the company's encouragement; being appointed manager of Planning & Budgeting and assisting Struan Anderson in developing the company's interests; being employed by RTZ Consulting in London from 1968; involvement in Bouganville Copper.
John Ralph talks about returning to Australia 1970 to become Finance Director of CRA (Conzinc Riotinto of Australia); CRA's position in the market; his interest in industrial relations and tax reform; his part in the formation of the International Federation of Accountants; corporate leadership and ethics; changes in corporate culture and organisational structure of CRA; his experience with the Australian Manufacturing Council; occupational health and safety; individual workplace agreements; improvement of relations between management and staff; continuous improvement and its impact on the company; directorships he took up after he retired from CRA; being on 6 Boards; working on the Tax Review for the Federal Government; his work for Melbourne's Olympic bid.
Recorded on June 8 and Dec. 13, 2006 at Toorak, Vic.
Digital master available
Timed summary (6 p.) and uncorrected transcript (typescript, 103 leaves).
Keywords: Ralph, John Theodore -- Interviews; CRA Limited; Financial executives -- Australia -- Interviews; Mineral industries -- Australia; Industrial relations -- Australia; Executives